Mercury and Selenium Trophic Transfer in the Mexican California Current Ecosystem Using a Top Predator as a Model - Maria Emilia Rechimont; Felipe Amezcua; Jorge Ricardo Ruelas-Inzunza; Roberto Cruz-Garcìa; Juan Roberto Felipe Vallarta-Zárate; Felipe Amezcua-Linares (Fishes, 2025)
Research on the trophic transfer of trace elements in food chains, particularly toxic elements like mercury (Hg) and essential elements like selenium (Se), is crucial for understanding their impact on human health. In this work, we assessed the transfer of Hg and Se in the blue shark (Prionace glauca), a top predator with economic importance. Muscle samples from sharks, as well as their main prey (squid, red shrimp, sardine, and mackerel), were analyzed for Hg and Se concentrations. The Hg levels of sharks were below the recommended legal limit for seafood consumption in Mexico (1 µg·g−1 ww), while Se levels were significantly lower than previously reported for the species. Biomagnification was evaluated in this species by calculating biomagnification factors (BMF) for Hg and Se based on predator-prey element concentrations. Hg showed a BMF of 2.8, indicating biomagnification, while Se had a BMF of 0.2, suggesting biodilution. Trophic transfer factor models supported these findings, showing a positive correlation of Hg concentration with trophic level and a negative correlation with Se. However, while a hazard quotient under one does not pose a risk for consumption, a Se:Hg molar ratio under one estimated in the muscle tissue indicates that Hg levels along this food web should be approached with caution.